2021
DOI: 10.3390/ijms22063143
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Distribution in Human Skin: Influence of Cytoskeletal, Polarity, and Centrosome-Related Machinery of Stratum basale Keratinocytes

Abstract: Melanin granules cluster within supra-nuclear caps in basal keratinocytes (KCs) of the human epidermis, where they protect KC genomic DNA against ultraviolet radiation (UVR) damage. While much is known about melanogenesis in melanocytes (MCs) and a moderate amount about melanin transfer from MC to KC, we know little about the fate of melanin once inside KCs. We recently reported that melanin fate in progenitor KCs is regulated by rare asymmetric organelle movement during mitosis. Here, we explore the role of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 65 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…This localization was shown to be dependent on cytoplasmic dynein and dynactin to aggregate melanokerasomes at the perinuclear region [ 74 ]. Also, it was recently shown that the apical distribution of melanin after being transferred to keratinocytes is regulated by the centrosome and centriolar satellites [ 75 ]. Importantly, microtubules and actin cytoskeleton networks seem to maintain melanokerasomes in the apical domain of proliferative keratinocytes, protecting these cells from UVR-induced damage.…”
Section: Melanin Processing Within Keratinocytesmentioning
confidence: 99%
“…This localization was shown to be dependent on cytoplasmic dynein and dynactin to aggregate melanokerasomes at the perinuclear region [ 74 ]. Also, it was recently shown that the apical distribution of melanin after being transferred to keratinocytes is regulated by the centrosome and centriolar satellites [ 75 ]. Importantly, microtubules and actin cytoskeleton networks seem to maintain melanokerasomes in the apical domain of proliferative keratinocytes, protecting these cells from UVR-induced damage.…”
Section: Melanin Processing Within Keratinocytesmentioning
confidence: 99%
“…It has been considered that melanin granules are positioned apically to provide protection against UVR-induced damage [ 3 , 36 ] A recent study showed that cell polarity and the movement of centrosomes and centriolar satellites are implicated in apical distribution of melanin within the human keratinocytes [ 41 ]. The previous study in several cetacean species has described the phenomena that melanin granules were arranged apically within keratinocytes [ 36 ] although the color of analyzed skin samples was not described.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the skin in flaps had lower melanocyte function than normal, undamaged skin. One possible explanation relates to the fact that melanocytes are confined to the human epidermis; therefore, when an incision is made for the flap, transient relative ischemia and hypothermia damage melanocytes [9,10]. This may be a reason why the flap melanin levels were observed to be lower than those of abdominal skin.…”
Section: Discussionmentioning
confidence: 99%